Mentoring as a Distributed Practice of Care: A Conversation - Silvia Gherardi; Michela Cozza; Laura Lucia Parolin (Sociologica)
The conversation that we perform seeks to foreground mentoring as a collegial and distributed practice of reciprocity, care, and support happening in the interstices of academia. We argue that mentoring in academia can be a distributed process by promoting a learning community of doctoral students who participate in the research life and other department or research group activities. Promoting such learning communities also entails encouraging reciprocal kindness and care in any relationship, vertical or horizontal.